Aplikasi Bokashi Eceng Gondok (Eichhornia crassipes) dan Fungi Mikoriza Arbuskula untuk Perbaikan Sifat Fisika Tanah Pasca Galian C dan Hasil Tanaman Cabai (Capsicum frustescens L.): Aplikasi Bokashi Eceng Gondok (Eichhornia crassipes) dan Fungi Mikoriza Arbuskula untuk Perbaikan Sifat Fisika Tanah Pasca Galian C dan Hasil Tanaman Cabai (Capsicum frustescens L.) - Cecep Hidayat; Asep Supriadin; Fantyana Huwaida’a; Yati Setiati Rachmawati (Universitas Bangka Belitung, 2020)
Post-mine sandpits with low physical, chemical, and biological properties glance to be used as an alternative to vegetable cultivation but require input technology in organic matter and application of FMA. The Research aimed to know the effect of AMF and water hyacinth bokashi (Eichhornia crassipes) on the improvement of physical soil properties growth and yield of Chili pepper (Capsicum frutescens L.) on post-mine sandpits soil. A field-polybag trial had been carried out using a randomized block design two factors with factorial pattern and three replications. The first factor was water hyacinth bokashi dosage (control, 15 t ha-1, 20 t ha-1, and 25 t ha-1). The second factor was AMF dosage (without inoculation, 5 g polybag-1, and 10 g polybag-1). The results showed that application AMF and water hyacinth bokashi improve the soil’s physical properties (bulk density, soil porosity, and soil permeability), harvest index, and the wet weight of fruit. The main effect of bokashi occurs on the amount of chlorophyll, as for the root infection degree affected by FMA inoculation. The experiment indicated that application AMF 5 g and water hyacinth bokashi 15 t ha-1 could be used in Chilli pepper cultivation on post-mine sandpits.